2019
DOI: 10.14202/vetworld.2019.1441-1447
|View full text |Cite
|
Sign up to set email alerts
|

Assessing farmers' perspective on antibiotic usage and management practices in small-scale layer farms of Mymensingh district, Bangladesh

Abstract: Background and Aim:Indiscriminate and injudicious use of antibiotics in layer farms is a common practice of Bangladesh for the compensation of Poor management practices and ignorance. Despite this scenario, there is no published documentation on antibiotic usage pattern and farm management practices in layer farms. This study was undertaken to understand the farmers’ perspective in small-scale layer farms regarding antibiotics usage and farm management.Materials and Methods:A questionnaire survey was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 24 publications
6
71
0
1
Order By: Relevance
“…They use antibiotics to prevent egg production fall, for treatment purposes and also for prophylaxis in suboptimal doses. Most of the small-scale layer farmers (94.16%) use antibiotics without prescription and do not maintain the withdrawal period of drugs [ 25 ]. Besides the farms, the poultry meat sellers in live bird markets (LBMs) also use different types of antibiotic to prevent unwanted mortality [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They use antibiotics to prevent egg production fall, for treatment purposes and also for prophylaxis in suboptimal doses. Most of the small-scale layer farmers (94.16%) use antibiotics without prescription and do not maintain the withdrawal period of drugs [ 25 ]. Besides the farms, the poultry meat sellers in live bird markets (LBMs) also use different types of antibiotic to prevent unwanted mortality [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…As many as 19 and ten different types of antibiotic usage have been recorded in the broiler and layer farms, respectively. The most commonly used antibiotics in both types of farming systems are ciprofloxacin, ampicillin, amoxicillin, trimethoprim, oxytetracycline, tylosin tartrate, tiamulin, norfloxacin, enrofloxacin, doxycycline, and colistin sulfate [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies show that most farmers (>60%) used antibiotics without the prescription of the veterinarians (24). Another study in Bangladesh among small-scale layer farms of Mymensingh district revealed that almost all (94%) farmers were using antibiotics without maintaining the minimum withdrawal period before marketing (25). Residues of ampicillin, ciprofloxacin and enrofloxacin have been detected in liver and meat of broilers (26).…”
Section: Discussionmentioning
confidence: 99%
“…FAO referred to farmers as "important frontline defenders" for the vital role they can play in stemming the spread of AMR by adopting good hygienic farm operations. Increasing awareness among farmers by imparting basic knowledge may help reduce the unnecessary and indiscriminate AMU in food animals (104); however, it can only be successful if adequate financial support and insurance packages are given to recuperate any loss in livestock farming (145). In most of the LMICs, small and marginal farmers often suffer huge economic losses due to disease outbreaks for meager investments on biosecurity and farm hygiene; these psychologically disadvantaged farmers can then be easily misled about the purported efficacy of antimicrobials for growth promotion and disease prevention by the unscrupulous push-sell of drug-marketing agencies.…”
Section: Raising Awareness Among Farmersmentioning
confidence: 99%
“…In most of the LMICs, small and marginal farmers often suffer huge economic losses due to disease outbreaks for meager investments on biosecurity and farm hygiene; these psychologically disadvantaged farmers can then be easily misled about the purported efficacy of antimicrobials for growth promotion and disease prevention by the unscrupulous push-sell of drug-marketing agencies. Inadequate veterinary healthcare facilities and limited drug regulations increase the magnitude of the problem in LMICs and, without reshaping these, efforts to bring sustainable change in farmers' behavior, knowledge, attitude, and practices may be futile (145). Changing farmers' behaviors or increasing their awareness for appropriate AMU in food animals requires multiple supportive measures, like incentives to the farmers raising livestock without antibiotics, subsidized insurance to make up for losses, the implementation of strict drug regulation, and the establishment of a strong network of veterinary healthcare facilities accessible to rural farmers in LMICs.…”
Section: Raising Awareness Among Farmersmentioning
confidence: 99%